2019
DOI: 10.2196/10020
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Health Records to Develop and Implement a Silent Best Practice Alert Notification System for Patient Recruitment in Clinical Research: Quality Improvement Initiative

Abstract: Background Participant recruitment, especially for frail, elderly, hospitalized patients, remains one of the greatest challenges for many research groups. Traditional recruitment methods such as chart reviews are often inefficient, low-yielding, time consuming, and expensive. Best Practice Alert (BPA) systems have previously been used to improve clinical care and inform provider decision making, but the system has not been widely used in the setting of clinical research. Objective … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…The following studies looked at using EHR in research (n=14)[9, 16, 27, 40-50] and development (n= 15). [20, 28, 31, 38, 40-43, 45, 47-52] Several studies looking at EHR in research showed its vast capabilities and positive implications.…”
Section: Resultsmentioning
confidence: 99%
“…The following studies looked at using EHR in research (n=14)[9, 16, 27, 40-50] and development (n= 15). [20, 28, 31, 38, 40-43, 45, 47-52] Several studies looking at EHR in research showed its vast capabilities and positive implications.…”
Section: Resultsmentioning
confidence: 99%
“…Best practice alerts (BPAs) are a growing tool that have been shown to improve health outcomes and reduce costs for multiple diseases and patient populations (Swedlund et al 2019 ; Bejjanki et al 2018 ). Implementing best practice alerts may help healthcare providers appropriately screen and place consults for our HVIP or even allow for automation of the referral process (Devoe et al 2019 ). Now that we have standard criteria for identifying eligible patients, we can use it to screen for youth who present to our EDTC with violent injuries as we develop a BPA.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] EHRbased clinical trial alerts (CTAs), which notify clinical personnel when a patient's EHR data meet presumptive criteria for enrollment in a clinical trial, have been utilized for many years. [8][9][10] CTAs are associated with higher recruitment yield and have improved cost-efficiency of clinical trials by reducing the time research staff spend on patient identification and screening. [11][12][13] EHR-based CTAs may be delivered to various recipients by various methods and can be used in combination with other recruitment strategies.…”
Section: Background and Significancementioning
confidence: 99%